Akuntabilitas Pelayanan Publik di Kantor Camat Batudaa Pantai Kabupaten Gorontalo - Yulis Alinti; Zuchri Abdussamad; Juriko Abdussamad (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to evaluate the accountability of public service delivery at theBatudaa Pantai Subdistrict Office, Gorontalo Regency, focusing on three key aspects:service standards, handling of nonconformities, and prioritization of user needs.Thestudy is motivated by community complaints regarding service delays, unclearprocedures, and a lack of responsiveness from public officials, which have led to adecline in public satisfaction. A descriptive qualitative approach was employed, withdata collected through interviews, observations, and documentation. Data validity wasensured using triangulation techniques. The findings indicate that the implementation of Standard Operating Procedures(SOPs) at the Batudaa Pantai Subdistrict Office has not been consistently applied,resulting in discrepancies between established regulations and actual practices. Although efforts have been made by public officials to address these inconsistencies,they have been hindered by limited infrastructure and facilities. Furthermore, the needsof the community have not been fully prioritized due to low responsiveness and limitedcapacity of the apparatus. In conclusion, public service accountability at the Batudaa Pantai Subdistrict Office remains suboptimal. Therefore, cesary to strengthenSOP implementation, improve complaint-handling meclnisia an enent servicedelivery more toward public needs.